Effect of Deletion of Ghrelin‐O‐Acyltransferase on the Pulsatile Release of Growth Hormone in Mice. (December 2015) - Xie, T. Y.; Ngo, S. T.; Veldhuis, J. D.; Jeffery, P. L.; Chopin, L. K.; Tschöp, M.; Waters, M. J.; Tolle, V.; Epelbaum, J.; Chen, C.; Steyn, F. J.
Abstract : Ghrelin, a gut hormone originating from the post‐translational cleavage of preproghrelin, is the endogenous ligand of growth hormone secretagogue receptor 1a (GHS‐R1a). Within the growth hormone (GH) axis, the biological activity of ghrelin requires octanoylation by ghrelin‐ O ‐acyltransferase (GOAT), conferring selective binding to the GHS‐R1a receptor via acylated ghrelin. Complete loss of preproghrelin‐derived signalling (through deletion of the Ghrl gene) contributes to a decline in peak GH release; however, the selective contribution of endogenous acyl‐ghrelin to pulsatile GH release remains to be established. We assessed the pulsatile release of GH in ad lib . fed male germline goat −/− mice, extending measures to include mRNA for key hypothalamic regulators of GH release, and peripheral factors that are modulated relative to GH release. The amount of GH released was reduced in young goat −/− mice compared to age‐matched wild‐type mice, whereas pulse frequency and irregularity increased. Altered GH release did not coincide with alterations in hypothalamic Ghrh, Srif, Npy or Ghsr mRNA expression, or pituitary GH content, suggesting that loss of Goat does not compromise canonical mechanisms that contribute to pituitary GH production and release. Although loss of Goat resulted in an irregular pattern of GH release (characterised by an increase in the number of GH pulses observed during extended secretory events), this did not contribute to a change in the expression of sexually dimorphic GH‐dependent liver genes. Of interest, circulating levels of insulin‐like growth factor (IGF)‐1 were elevated in goat −/− mice. This rise in circulating levels of IGF‐1 was correlated with an increase in GH pulse frequency, suggesting that sustained or increased IGF‐1 release in goat −/− mice may occur in response to altered GH release patterning. Our observations demonstrate that germline loss of Goat alters GH release and patterning. Although the biological relevance of altered GH secretory patterning remains unclear, we propose that this may contribute to sustained IGF‐1 release and growth in goat −/− mice.